Halal compliance in poultry industry: a review of regulatory system in Malaysia - Hashim, Husna; Md Saad, Norma; Khalid, Haniza; Laluddin, Hayatullah (Human Resource Management Academic Research Society, 2019)
Halal food compliance is a critical issue for Muslim consumers, hence becomes a major challenge for Malaysia as a leader in the development of global halal market. This study provides a review of the regulatory system in the poultry industry practised in Malaysia and explores common problems faced by the authorities in enforcing halal compliance among poultry slaughtering and processing businesses. Halal compliance describes the ability of the businesses to act according to halal requirements as outlined by the halal authority. Their level of compliance depends on the effectiveness of the enforcement efforts. A content analysis approach was employed to gather adequate data for the purpose of this study. The results show that securing halal compliance requires collective efforts and coordination between the regulatory bodies involved in the industry. This study provides better understanding of control mechanism in halal industry in general, which helps in securing halal authenticity and subsequently halal integrity throughout food supply chains as envisioned in the Halal Industrial Master Plan (HIMP).